2015
DOI: 10.1111/petr.12596
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pediatric Health Information System database to study the trends in the incidence, management, etiology, and outcomes due to pediatric acute liver failure in the United States from 2008 to 2013

Abstract: Data were collected of children admitted with ALF to 16 US pediatric liver transplant centers from 2008 to 2013 using the PHIS for a retrospective analysis of PALF trends. Patient data linked to the principal diagnosis code for acute necrosis of the liver (570.00) were analyzed for the following: demographics, regional differences, changes over time, pharmaceutical trends, procedural trends, associated diagnoses, and patient outcomes. In 52.5% of 583 patients who met the selection criteria for PALF, the etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 28 publications
(49 reference statements)
1
31
2
Order By: Relevance
“…Our study found that children with ALF experienced a shorter LOS, as opposed to the previously reported longer LOS 5 . Though historically associated with poor outcomes, outcomes for pediatric patients with ALF have improved, both in medical management alone and after liver transplantation 27 . Furthermore, a recent study of children with ESLD due to chronic disease suggests that these children may be further disadvantaged by the presence of frailty, a marker of morbidity not adequately captured by conventional laboratory tests 28 .…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Our study found that children with ALF experienced a shorter LOS, as opposed to the previously reported longer LOS 5 . Though historically associated with poor outcomes, outcomes for pediatric patients with ALF have improved, both in medical management alone and after liver transplantation 27 . Furthermore, a recent study of children with ESLD due to chronic disease suggests that these children may be further disadvantaged by the presence of frailty, a marker of morbidity not adequately captured by conventional laboratory tests 28 .…”
Section: Discussioncontrasting
confidence: 48%
“…Frailty was shown to be present in 24% of their cohort of children and represents a possible mechanism by which children with chronic liver disease would experience a longer LOS compared to children with ALF. Children with ALF are likely to be previously healthy prior to referral for liver transplantation and may be more likely to withstand the acute stress of liver transplantation 27 . Finally, our analysis is subject to survival bias due to both the increased waitlist mortality and post‐transplant mortality of children with ALF compared to those with chronic liver disease 29 …”
Section: Discussionmentioning
confidence: 99%
“…The low rate of hepatitis B in children may possibly be attributed to the successful national HBV vaccination program, which has been in effect since 1998. In most countries in northern Europe, and in North and South America (2,4,10,23,24), indeterminate causes predominate in ALF in childhood, whereas acetaminophen toxicity was the most common identifiable cause of ALF in older children. In our study, etiology remained indeterminate in 33% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in our understanding of congenital diseases that lead to liver failure in the pediatric population, there are still a significant number of infants that present with late complications related to ESLD. The etiology of liver failure during the neonatal period and early infancy in this patient population includes metabolic disorders (tyrosinemia etc), biliary atresia, GALD, infection, and hypoxia‐ischemia‐related hepatopathy . The most common presentation is jaundice and hypoglycemia followed by renal failure, bleeding, and encephalopathy .…”
Section: Introductionmentioning
confidence: 99%